Medication error reporting – An insight among final-year MBBS students and interns - Praneeth Reddy Onteddu; Shravya Edavaluru; Bhuvaneshwari Edavaluru; Mary Rohini Pentareddy; Chaitanya Kandula (Asian Journal of Medical Sciences, 2023)
Background: Medication errors can be defined as avoidable errors that can occur while prescribing, transcribing, dispensing, or administering a drug to a patient. Medication errors lead to mortality and morbidity of varying severities in patients. They also impose a heavy financial burden on the health-care sector. This study was conducted to compare three aspects of medication errors – Awareness, Outlook, and reporting, between two demographic groups, namely, interns and final-year MBBS students. Aims and Objectives: The objectives of this study were to evaluate the level of awareness about medication errors, the outlook toward medication errors and the medication errors reporting among MBBS students and Interns. Materials and Methods: A questionnaire was handed out to 500 people and it had questions related to awareness, outlook, and reporting of medication errors. Out of these 500 people, the number of respondents was 425 and they were grouped into various sub-categories based on their responses. Results: 30.6% of the respondents had sufficient awareness, 44.9% of the respondents had a good outlook, and 27.5% were reporting medication errors. The results also depicted that the Interns have better awareness and better practice of reporting when compared to final-year MBBS students. On the other hand, final-year MBBS students had a better outlook toward medication errors than Interns. Conclusion: It can be concluded from this study that more education and training in medication error reporting is essential right from the undergraduate level. There should also be well-established reporting systems in hospitals.